"I am trying to practice good teaching": Reconceptualizing eportfolios for professional development in vocational higher education. (23rd March 2016) - Winberg, Christine; Pallitt, Nicola
Abstract: Teaching portfolios have become increasingly important to university teachers. Portfolio requirements for the appointment or promotion of academic staff recognize that the assessment of teaching practice requires more depth and detail than a candidate's academic CV generally affords. The focus of this study is the electronic teaching portfolios, developed for purposes of promotion, in a vocational higher education context. Data were obtained from candidates' eportfolios, from precourse and end‐of‐course surveys, as well as from eportfolio assessors' formative and summative feedback. The analysis of the data reveals tensions arising from portfolio building in the particular context of vocational higher education. The nature of the vocational field impacts not only on teaching and learning practice, but on how academic staff choose to present their practice in an eportfolio. The paper argues that the constraints and enablements of context, including the disciplinary context, as well as the possibilities and limitations of agency, will strongly influence the purposes of eportfolio development and the extent to which university teachers can exercise agency in the creation of an eportfolio in a "high stakes" context. The findings can help university appointments and promotions committees, as well as educational developers, to better understand these enablements and constraints in order to inform policy and implementation.